2021
DOI: 10.1186/s13660-021-02549-3
|View full text |Cite
|
Sign up to set email alerts
|

Data analysis of heavy metal content in riverwater: multivariate statistical analysis and inequality expressions

Abstract: The purpose of this paper is to use multivariate statistical methods with asymmetric distributions approach, chemical analysis, and inductively coupled plasma–mass spectrometry (ICP-MS) device. We investigate data of heavy metal content from Akcay Riverwater to the Mediterranean involving Finike sea coast at Turkey. We determine the chemical content, origin of heavy metals of the surface water in Akcay River, which flows into the Mediterranean realted to the above-mentioned region by multivariate statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…37−43 Nevertheless, Pb concentrations in the current basin were higher than in Euphrates and Akcay rivers. 39,40 Cr(VI) showed higher concentrations in the present basin than in Euphrate and Catalan rivers. 39,41 As concentrations were higher than those of the Akcay and Catalan rivers.…”
Section: Characteristics Of the Esil River Basin's Water Quality 311 ...mentioning
confidence: 57%
See 1 more Smart Citation
“…37−43 Nevertheless, Pb concentrations in the current basin were higher than in Euphrates and Akcay rivers. 39,40 Cr(VI) showed higher concentrations in the present basin than in Euphrate and Catalan rivers. 39,41 As concentrations were higher than those of the Akcay and Catalan rivers.…”
Section: Characteristics Of the Esil River Basin's Water Quality 311 ...mentioning
confidence: 57%
“…39,41 As concentrations were higher than those of the Akcay and Catalan rivers. 40,41 Overall, the HM pollution of the Esil river basin could be categorized as a medium contaminated level compared to water basins of other industrial counties. S2 depicts the four HMs' monthly median concentrations in the 15 sites of the Esil river basin.…”
Section: Characteristics Of the Esil River Basin's Water Quality 311 ...mentioning
confidence: 99%
“…Before conducting the factor analysis, the sampling adequacy of the data for the factor analysis was tested using the Kaiser-Meyer-Olkin test, and the test statistics revealed that the data is suitable [41]- [44] (Table 7). The measure of sampling adequacy is expected to be greater than 0.5 for the suitability of the data for the factor analysis [35], [45]- [50]. In this context, the value that was calculated as 0.52 revealed the suitability of geochemical data for the factor analysis.…”
Section: Factor Analysismentioning
confidence: 99%
“…Para comparar la efectividad del proceso de adsorción en los experimentos, se calculó el valor de la capacidad de adsorción (q) de la biomasa con la ecuación [1]:…”
Section: Tabla 1 Variables Y Sus Niveles Para El Diseño Experimentalunclassified
“…Una problemática ambiental de gran relevancia en el mundo ha sido la contaminación de mares, ríos y otros afluentes por metales pesados [1,2]. Entre estos metales, Cr (VI) se clasifica como uno de los más peligrosos y tóxicos [3][4][5][6][7].…”
Section: Introductionunclassified